Pengaruh Pengalaman Kerja dan Disiplin Kerja Terhadap Pengembangan Karir dengan Prestasi Kerja Sebagai Variabel Intervening Pada Puskesmas Alai Kota Padang - Maya Patricia Chandra; Marta Widian Sari; Yosi Puspita Sari (GLOBAL SCIENTS PUBLISHER, 2026)
The purpose of this study was to determine how much influence work experience and work discipline have on career development with job performance as an intervening variable at Puskesmas Alai, Padang City. The data analysis method used a questionnaire, with a sample of 42 respondents. The analysis method used is path analysis using the SmartPLS application. Based on the results of the study, it shows that there is a positive and significant influence between work experience and job performance. There is a positive and significant influence between work discipline and job performance. There is a positive and insignificant influence between work experience and career development. There is a negative and insignificant influence between work discipline and career development. There is a positive and significant influence between job performance and career development. There is a positive and significant influence between work experience and career development with job performance as an intervening variable. There is a positive and significant influence of work discipline on career development with job performance as an intervening variable.